Effect of atmospheric pollutants on the corrosion of high power electrical conductors: Part 1. Aluminium and AA6201 alloy - Vera, Rosa (2006)
The aim of this study was to evaluate the joint effect of marine and industrial pollutants on the atmospheric corrosion of aluminium and its AA6201 alloy. Weight loss was determined after 4, 11, 16 and 24 months exposure being morphology and attack intensity analysed through SEM-EDX. Both materials showed the most intense attack for the highest SO2 contents. Good correlation among weight loss, attack depth and tensile strength to rupture with time and with pollutant contents was determined for both materials in most sites. The cause for low aggressiveness of the heaviest Cl- polluted atmosphere on aluminium was electrochemically demonstrated.